2013
DOI: 10.1093/cid/cit125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of HIV-1 Minority Variants

Abstract: Technologic advances in human immunodeficiency virus type 1 (HIV-1) sequencing have revolutionized the study of antiretroviral drug resistance and are increasingly moving from the laboratory to clinical practice. These techniques are able to detect HIV-1 drug resistance mutations present at low frequencies not detectable by current HIV-1 genotyping assays. For a number of commonly used antiretroviral medications, such as nonnucleoside reverse transcriptase inhibitors, the detection of these drug-resistant mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 103 publications
(111 reference statements)
1
42
0
Order By: Relevance
“…As described above, DeepGen HIV detected additional (minority) HIV-1 drug resistance mutations and non-R5 variants compared to population sequencing; however, the clinical relevance of these minority members of the viral population is still under debate (33,51,55,57,(127)(128)(129). It is reasonable to assume that under appropriate selection (i.e., drug pressure), minority variants carrying drug resistance mutations will eventually outcompete other members of the viral population, and the earlier these mutations are detected, the sooner the proper strategy can be defined to control the growth of these viruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, DeepGen HIV detected additional (minority) HIV-1 drug resistance mutations and non-R5 variants compared to population sequencing; however, the clinical relevance of these minority members of the viral population is still under debate (33,51,55,57,(127)(128)(129). It is reasonable to assume that under appropriate selection (i.e., drug pressure), minority variants carrying drug resistance mutations will eventually outcompete other members of the viral population, and the earlier these mutations are detected, the sooner the proper strategy can be defined to control the growth of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that under appropriate selection (i.e., drug pressure), minority variants carrying drug resistance mutations will eventually outcompete other members of the viral population, and the earlier these mutations are detected, the sooner the proper strategy can be defined to control the growth of these viruses. However, the threshold for the identification of significant low-level variants may be mutation and/or antiretroviral drug dependent (32); therefore, early detection of drug-resistant HIV-1 minority variants, or non-R5 variants in the case of CCR5 antagonists, may contribute to the prediction of clinical or treatment outcome (32,36,57,63,127). Additional effort, most likely in the form of longitudinal studies, is needed to better understand the clinical relevance of these minority HIV-1 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of coverage obtained (typically several thousands to tens of thousands of reads per sample [20,21]) can be used to detect lowfrequency variants and to study within-host HIV evolution (22). Several studies have clearly demonstrated that the presence of low-frequency drug-resistant variants, particularly those with NNRTI resistance, can negatively affect treatment outcomes (20,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…It is noteworthy that the replicative as well as transmission properties of mutant and wild type variants are highly different. For example, certain data suggest that some drug resistant variants possess reduced replicative capacity in comparison with wild-type virus and therefore, drug resistant infection might be of some virological benefit to the hosts' immune system [39][40][41] .…”
Section: History and Mechanisms Of Anti-retroviral Drug Resistance (Amentioning
confidence: 99%